Gemcitabine-loaded Ca2+-crosslinked high-amylose starch beads as intratumoral depot candidates: microporosity, release, and in vitro activity - Avci, Hakan; Ceylan, Deniz; Aytekin, Nil Azra (TAYLOR & FRANCIS INC, 2025)
Pancreatic ductal adenocarcinoma (PDAC) motivates localized drug-delivery strategies that increase intratumoral exposure while limiting systemic toxicity. Here, we report spherical high-amylose starch beads prepared by droplet gelation and Ca2+ ionotropic crosslinking as a simple, water-based depot platform. The beads preserved spherical geometry and displayed an interconnected microporous interior by SEM. FTIR supported Ca2+-OH interactions within the starch network and non-covalent (physical) loading of gemcitabine without evidence of new covalent bonds. In PBS (pH 6.6, 37 degrees C), formulations with 10-15% CaCl2 maintained structural integrity yet underwent enzyme-responsive erosion in alpha-amylase (approximate to 8-10 days), suggesting residence times compatible with intratumoral depots. HPLC-UV enabled quantification of gemcitabine encapsulation efficiency (EE = 4.14%), corresponding to similar to 3.53 mu g per bead (30 beads analyzed). In vitro release under sink conditions exhibited a burst-to-plateau profile with near-quantitative mass recovery (approximate to 100% of the loaded dose within hours). Preliminary cell studies were performed with PANC-1 to assess functional delivery. Collectively, these data indicate that Ca2+-crosslinked starch beads are in vitro tolerable, solvent-free, and injection-ready candidates for intratumoral chemotherapy. Limitations include the modest EE and rapid early release; avenues to address these (e.g., network densification or secondary coatings and process optimization) are outlined, together with the need for in vivo evaluation of residence, pharmacokinetics, and safety.
Keywords: High-amylose starch; ionotropic gelation; calcium crosslinking; intratumoral depot; gemcitabine; pancreatic cancer; CROSS-LINKING; BEHAVIOR; Polymer Science